Tinjauan Filosofis Pragmatisme John Dewey Terhadap Persoalan Sekularisasi Agama: John Dewey's Philosophical Review of Pragmatism on the Problem of the Secularization of Religion - Santiago, Dominiq Fransz; Asnawi, Naupal (Jurnal Filsafat Indonesia, 2024)
This article attempts to elaborate on John Dewey's views on the practical-pragmatic role of religion, and looks at the importance of reinterpreting traditional ideas of religion, such as faith and God, so that people would not get false conception about religion. Thus, using a critical analysis method of literature references and through the views of John Dewey, this paper aims to provide an understanding of the strategic role of religion in society, apart from being a system of societal beliefs that shapes individual ethical behavior, as well as a basis for building societal morals, which through this understanding, it is hoped that we can stem secularization which is increasingly diminishing the role of religion in society. Religion can be said to be society's moral compass which helps construct society's ethical life. As time and technology develop, religion also develops through various forms in an effort to adapt. The recent problem is that society from a secular perspective tends to assume that morality can be achieved outside of religion. Secularization is inevitable because religion is seen as something that is often used for political purposes rather than as a moral guidance for society. Therefore, religion today is seen more as a private matter, and should not be included in public affairs. This phenomenon is adapted to the view of secularism which emphasizes rational and logical thinking, while religion is closely related to sacred values that are supernatural. The conclusion is that through Dewey's Pragmatism, we can see that religion pragmatically is a moral guideline for society and a belief system that carries the values of fairness, justice, peace, so as to create a dynamic and harmonious society amidst the various differences that exist.